Market study of financial mechanism for climate risk management in the livestock sector in Guatemala - YAPU Solutions GmbH (2022)
This document presents the market study results to identify relevant information, characteristics, and conditions of an enabling environment for climate resilience financial services in livestock in the Peten, Izabal, Jalapa, Jutiapa, and Santa Rosa departments of Guatemala. It was developed by YAPU Solutions as a consultancy deliverable for the Alliance Bioversity International and the International Center for Tropical Agriculture (CIAT) and is part of the Livestock, Climate, and System Resilience initiative of the CGIAR portfolio.